MS analytical strategies for identifying aminophospholipid oxidation and their correlation with immunity - Colombo, Simone (2019)
The biological relevance of biochemically modified phosphatidylethanolamines (PE) and phosphatidylserines (PS), generally named aminophospholipids (APL) has been increasingly acknowledged over the last two decades. Oxidized, glycated and carbonylated APL were detected in physiological and pathological contexts and it is recognized that they play important biological roles in cell death, inflammation and blood coagulation, among others. However, the bioanalytical characterization of modified APL remains an emerging field that has not been deeply explored yet. The present Thesis had as main objective to advance and deepen the current knowledge on the interplay between APL and biochemical stress. To do so, it aimed to achieve a deep structural characterization of oxidized and glyco-oxidized APL, and to unravel the modulatory effect of oxidized APL on subsets of immune cells. In parallel, it evaluated how oxidative, glycative, and lipoxidative stress affected the biosynthesis of APL and other phospholipid classes in endothelial cells. The structural characterization of oxidized and glyco-oxidized APL, based on in vitro biomimetic models, was performed either by electrochemical oxidation coupled to MS (EC-MS) or using liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis. In a first study, 3 PE standards were oxidized by EC oxidation using a flow‐through cell system, and the oxidation products were identified online by electrospray ionization (ESI-)MS/MS. Both long chain and short chain oxidation products of PE were identified within minutes. The EC‐ESI‐MS/MS platform was highlighted as an innovative method able to rapidly mimic the peroxidation of PE mediated by partially reduced oxygen species (ROS). Additionally, complex mixtures of oxidized and glyco-oxidized APL were analysed by C30 reversed phase LC (RPLC) and high-resolution MS and MS/MS. The C30 reversed phase LC allowed functional and positional isomers of short and long chain oxidation products to be separated, along with glyco-oxidized APL bearing oxidative modifications on the glucose moiety and on the fatty acyl chains. HCD MS/MS spectra provided specific MS/MS fingerprinting and unequivocal structural characterization of the modified APL derivatives. This elucidation of MS/MS fingerprints of structural isomers of modified APL, achieved by EC-ESI-MS/MS and C30 RPLC-MS/MS, can ultimately be translated into targeted methods for the detection of modified APL in biological and clinical samples. In parallel, the project of this Thesis meant to shed light on the putative correlation between oxidized APL and the modulation of the immune system. Flow cytometry was used to evaluate the ability of oxidized arachidonoyl-PE (OxPAPE) and PS (OxPAPS) to modulate the inflammatory phenotype of monocytes subsets and myeloid dendritic cells in human peripheral blood. Overall, OxPAPE promoted the inflammatory response in blood immune cells, whereas OxPAPS was found to mitigate inflammation in lipopolysaccharide-activated cells. These results showed the importance of OxPAPE and OxPAPS as modulators of the inflammatory response and demonstrated their possible contribution to the onset and resolution of human diseases related to oxidative stress and inflammation. In a complementary approach, a lipidomic method based on hydrophilic interaction LC-tandem MS (HILIC-LC-MS/MS) was applied to quantify APL and other classes of phospholipids in endothelial cells treated with H2O2, high glucose and HNE. H2O2 induced a more acute adaptation of the phospholipid profile than glucose or HNE, and unsaturated phospholipid molecular species were up-regulated after 24 h incubation with H2O2, while an opposite trend was generally observed in glucose- and HNE-treated cells. The results unveiled specific phospholipid signatures occurring in endothelial cells in response to characteristic types of stress. Overall, the studies presented in this Thesis reported a deep structural characterization of modified APL through innovative approaches based on biomimetic methods and cutting-edge LC-MS/MS technologies, contributed to further understand the biological relevance of oxidized APL in immunity, health and disease, and showed that the cellular APL profile is significantly responsive to oxidative stress and glucolipotoxicity. This new bioanalytical knowledge contributes to revealing the implications of modified APL in inflammatory diseases and opens new avenues of research focused on the identification of biomarkers of noncommunicable and highlydebilitating pathologies as cancer, diabetes, cardiovascular diseases and atherosclerosis.